Sports nutrition: fluid, electrolytes and minerals - Noakes, T. D. (1995)
- Fluid requirements of athletes - Detrimental effects of 'voluntary' dehydration during exercise - Other electrolytes and minerals - Carbohydrate requirements during exercise - Optimal fluid replacement during exercise